Modification of Polyketone via Chlorodimethylsilane-Mediated Reductive Etherification Reaction: A Practical Way for Alkoxy-Functional Polymers - Luleburgaz, Serter; Hizal, Gurkan; Tunca, Umit; Durmaz, Hakan (American Chemical Society (ACS), 2021)
This study describes a straightforward post-polymerization modification (PPM) methodology from polyketone via chlorodimethylsilane (CDMS)-mediated reductive etherification reaction (RER). The polyketone platform was prepared via acyclic diene metathesis (ADMET) polymerization and reacted with a variety of alcohols in the presence of CDMS to create a wide range of polymers possessing pendant functional-alkoxy structures under mild conditions. The effect of parameters such as solvents and the amount of reactants on RER were studied. We have also explored the effect of other silane compounds on RER, none of which provided as high efficiency as the CDMS-mediated one. It has been found that the primary alcohols yielded corresponding alkoxy structures in high efficiencies, high isolated yields, and a wide range of functional group tolerance. It was also found that the formation of polyalcohol was inevitable, to some extent, during the RERs in addition to the alkoxy-functional polymers. All the polymers obtained were characterized in detail by various spectroscopic measurements, and a mechanistic aspect was also presented to evaluate the product distributions. Since operationally simple chemical methods, with a high yield and functional group tolerance, that can be easily adapted to the macromolecular level are always desired in synthetic polymer chemistry, this study promises remarkable opportunities for synthesizing functional polymers and may pave a way for the development of a novel metal-free PPM method.